2021
DOI: 10.3390/jcm10143051
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Radiological Studies on Visualization of Gubernaculum Tracts of Permanent Teeth

Abstract: The eruption pathway from the dental follicle to the gingiva for permanent teeth is known as the gubernaculum tract (GT), a physiologic structure thought to play a role in tooth eruption. Cone beam computed tomography and multi-detector computed tomography have recently been used to visualize the GT, with the results indicating that this structure might be related to the normal eruption of teeth. By contrast, curved and/or constricted GTs may lead to abnormal tooth eruption. In addition, complex odontomas have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Additionally, we had a Ds individuals group in our study for which we evaluated common eruption disturbances (n = 213/338-63%) associated with this syndrome, which had a major influence on our 338 impacted or delayed/unerupted teeth [5,7,19,20]. According to the literature, GC absence or anatomical deformation could be possibly associated with various obstructive odontogenic tumors, such as compound or complex odontomas, mesiodens, or adenomatoid odontogenic tumors, which is demonstrated in our results [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, we had a Ds individuals group in our study for which we evaluated common eruption disturbances (n = 213/338-63%) associated with this syndrome, which had a major influence on our 338 impacted or delayed/unerupted teeth [5,7,19,20]. According to the literature, GC absence or anatomical deformation could be possibly associated with various obstructive odontogenic tumors, such as compound or complex odontomas, mesiodens, or adenomatoid odontogenic tumors, which is demonstrated in our results [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 52%
“…Through the years, studies demonstrated that GC structures can be visualized on panoramic and dental radiographs, although some diagnoses propose that the two-dimensional characteristics of dental radiographs would make it difficult to visualize or measure some GC aspects such as length, diameter, pathway, deformation, and/or obliteration. Therefore, recent studies introduced CBCT as a justified imaging examination to evaluate GC presence and its possible disturbances such as impacted or delayed/unerupted teeth that will influ-ence clinical pediatric dentistry, orthodontics planning, and oral and maxillofacial surgical treatment due to its specificity in different images [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, odontomas are often surrounded by thin connective tissue, consistent with the dental follicle [1]. This soft tissue capsule is close to or partially integrated with adjacent dental follicle, as has been frequently noted in radiological examinations, particularly in the widely used cone beam computer tomography [20,21,22]. Thus, we assumed that epithelial cross-linking between the soft tissue capsule of odontoma and the adjacent normal dental follicle may delay or prevent spontaneous tooth eruption.…”
Section: Discussionmentioning
confidence: 97%
“…( 6 ) on 598 CBCT samples, the authors detected gubernacular canal in 542 (90.6%) cases, which is consistent with the results found in the present study and the review study by Oda et al . ( 20 ).…”
Section: Discussionmentioning
confidence: 99%